2019
DOI: 10.1002/1873-3468.13702
|View full text |Cite
|
Sign up to set email alerts
|

Programmed ubiquitin acetylation using genetic code expansion reveals altered ubiquitination patterns

Abstract: Edited by Michael IbbaUbiquitination is a post-translational modification (PTM) capable of being regulated by other PTMs, including acetylation. However, the biological consequences of acetylated ubiquitin (acUb) variants are poorly understood, due to their transient nature in vivo and poor characterization in vitro. Since Ub is known to be acetylated in human cells, we produced all possible acUb variants using genetic code expansion. We also developed a protocol that optimizes acetyl-lysine addition to minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…The lysine residue is an important amino acid in posttranslational protein modifications 26‐28 . Acetylation and ubiquitination of lysine residues determine enzyme activity, protein–protein interaction, and stability 29‐31 . We have shown that K141 in FBXL19 can be acetylated by CBP 20 .…”
Section: Discussionmentioning
confidence: 92%
“…The lysine residue is an important amino acid in posttranslational protein modifications 26‐28 . Acetylation and ubiquitination of lysine residues determine enzyme activity, protein–protein interaction, and stability 29‐31 . We have shown that K141 in FBXL19 can be acetylated by CBP 20 .…”
Section: Discussionmentioning
confidence: 92%
“…Acetylated ubiquitin acUbK63 CyPet was expressed in E. coli BW25141­(λDE3) as previously established . All acetylated ubiquitin proteins were expressed like His-TEV constructs expressed previously . Briefly, after a fresh co-transformation of the orthogonal translation system and the acUbKx CyPet construct of interest, a colony was transferred into selective Luria broth (LB) (30 μg/mL kanamycin, 34 μg/mL chloramphenicol, and 0.2% glucose) and grown at 37 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…However, the acetyl-lysine side chain is longer and less polar and has the potential to form more extensive hydrophobic contacts than glutamine, suggesting glutamine substitution may not be indicative of the full effects of acetylation. Recently, many acetylated proteins, , including Ub, , have been produced in Escherichia coli using genetic code expansion. Reassignment of the amber stop codon (UAG) and the use of tRNA pyl‑opt enable a fast and accurate way to produce homogeneous acetylated proteins in vitro and have been applied in vivo .…”
mentioning
confidence: 99%
“…Ub activity can be further regulated by additional PTMs, e.g. acetylation, phosphorylation and SUMOylation ( Koyano et al, 2014 ; Morimoto and Shirakawa, 2016 ; Lamoliatte et al, 2017 ; Lacoursiere et al, 2020 ). For example, all Ub lysine residues (except K29) are acetylated under differing cellular conditions ( Choudhary et al, 2009 ; Elia et al, 2015 ; Lacoursiere et al, 2020 ).…”
Section: Mass Spectrometry Approaches For the Identification Of Carba...mentioning
confidence: 99%
“…acetylation, phosphorylation and SUMOylation ( Koyano et al, 2014 ; Morimoto and Shirakawa, 2016 ; Lamoliatte et al, 2017 ; Lacoursiere et al, 2020 ). For example, all Ub lysine residues (except K29) are acetylated under differing cellular conditions ( Choudhary et al, 2009 ; Elia et al, 2015 ; Lacoursiere et al, 2020 ). Ohtake et al, 2015 demonstrated that when endogenous Ub is acetylated at K6 and K48, this does not affect the ability of Ub to conjugate with substrate protein but inhibits the elongation of K11, K48 and K63-linked Ub-chains by several E2 enzymes (by neutralising the lysine residue positive charge involved in non-covalent interaction of Ub with specific E2s).…”
Section: Mass Spectrometry Approaches For the Identification Of Carba...mentioning
confidence: 99%